ANALISIS PRAGMATIK WACANA KARIKATUR, TINJAUAN ASPEK KEBAHASAAN - Slamet Supriyadi (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to describe (1) the types of speech acts and implicatures in caricature discourse; (2) the linguistic aspects inherent in caricature discourse and; (3) caricature readers' understanding of the social functions in caricature discourse. The research methodology used is descriptive qualitative research. Data collection techniques used interviews, observation and document analysis. The sampling technique used was purposive sampling technique. Data validity was validated by using data source triangulation. Then the analysis model uses an interactive model from Miles and Huberman. The results showed that many caricatures were drawn mainly to put forward constructive ideas about existing issues and to emphasize the humorous function. The types of speech acts utilized in caricature drawings are directive, commissive, expressive, and permissive speech acts. The linguistic aspects utilized in caricature discourse are, phonological aspects in the form of anomatope or sound imitation, words, phrases, sentences, and discourse. In the end, readers and caricature makers often have different understandings of the social function of caricature discourse texts. They have different understandings and interpretations of the meaning contained in the text and images of caricatures in relation to constructive criticism. Keyword: Language Aspects; Implicature; Pragmatics; Speech Acts